Developments and Challenges for Sustainable Productivity of Goats in Mixed Production Systems of East Africa - Komwihangilo, D M; Chenyambuga, S W; Temu, V W; Mushi, D (Annals of Arid Zone, 2016)
Goats in East Africa are mostly reared under the traditional goat management systcms whereby majority of indigenous goats, popularly known as the Small East African (SEA) goats, are kept. These provide meat goat that ranks second to beef in sales and consumption in the region. In more recent years crossbred goats of the indigenous strains and some Europea breeds have been on an increase with the result of dual-purpose goats that yield relatively higher quantities of meat and milk than the local goats. On the other hand, efforts for finding appropriate feeding regimes that are both economical and sustainable have also been sought with varying achievements in the diverse farming systems. Equally, the marketing aspects of live animals, milk and meat from goats have also been studied with various outputs and recommendations to stakeholders in research, agricultural extension and policy. In this paper, the developments in goat production and challenges facing the productivity of these animals are presented. Examples are cited from the mixed production systems of Tanzania and elsewhere in the Eastern Africa region. Similarly, recommendations for sustainable productivity of goats in the mixed systems are also given.